2012
DOI: 10.1177/0022034512450174
|View full text |Cite
|
Sign up to set email alerts
|

Caries Resistance as a Function of Age in an Initially Caries-free Population

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. AbstrActUsing data from the Center for Oral Health Research in Appalachia Study, we examined variability in susceptibility to dental caries among children and adolescents in rural Appalachia. Among 210 participants who were caries-free at the initial visit, age at the baseline visit can be used as a proxy for the degree of caries resistance; probability of caries development at the tooth level decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“… 22 Although the risk of new-onset caries is higher in individuals with more previous caries experience, 16 , 23 the risk is not zero in individuals without previous caries experience. 24 In this study, among children without baseline dmft, there was a statistically significant difference in DI-S between those with new-onset caries and those without new-onset caries. It has been suggested that oral hygiene status is useful to predict new-onset caries in individuals without previous caries experience.…”
Section: Discussionmentioning
confidence: 49%
“… 22 Although the risk of new-onset caries is higher in individuals with more previous caries experience, 16 , 23 the risk is not zero in individuals without previous caries experience. 24 In this study, among children without baseline dmft, there was a statistically significant difference in DI-S between those with new-onset caries and those without new-onset caries. It has been suggested that oral hygiene status is useful to predict new-onset caries in individuals without previous caries experience.…”
Section: Discussionmentioning
confidence: 49%
“…The variations between the findings of the studies may be related to many factors such as the sample size and the method by which dental caries was examined, in addition to the environmental and the genetic factor (22) . In addition the Ms fraction represented the largest fraction of DMFs among all the study samples, especially among the oldest adult who recorded the highest Ms which could be due to the fact that dental caries is an irreversible process and accumulative in nature with ageing on one hand and to the insufficiency of the planed preventive programs especially among the old adults who had poor dental knowledge as well as oral health, didn't receive an optimal dental care and had complicated past dental history (23) , In addition to that, they were prefered tooth extraction over restorations because there were several barriers to self-care and professional care. (24) .…”
Section: Discussionmentioning
confidence: 94%
“…A previous study suggested that the increment of DMFT was observed not only among those who experienced caries in childhood but also among those who did not [ 20 ]. Although those who experienced more caries were at a higher risk [ 18 , 22 ], the risk for those who did not experience caries was not zero [ 23 ]. Second, the high risk population is smaller than the low risk population.…”
Section: Discussionmentioning
confidence: 99%